Measurement of VH, H -> b(b)over-bar production as a function of the vector-boson transverse momentum in 13 TeV pp collisions with the ATLAS detector - Bortoletto, D; Aaboud, M; Aad, G; Abbott, B; Ambroz, L; Artoni, G; Balunas, WK; Barr, AJ; Beresford, L; Cooper-Sarkar, AM; Frost, JA; Gallas, EJ; et al. (Springer, 2019)
Cross-sections of associated production of a Higgs boson decaying into bottomquark pairs and an electroweak gauge boson, W or Z, decaying into leptons are measured as a function of the gauge boson transverse momentum. The measurements are performed in kinematic fiducial volumes defined in the ‘simplified template cross-section’ framework. The results are obtained using 79.8 fb−1 of proton-proton collisions recorded by the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of 13 TeV. All measurements are found to be in agreement with the Standard Model predictions, and limits are set on the parameters of an effective Lagrangian sensitive to modifications of the Higgs boson couplings to the electroweak gauge bosons.